2008
DOI: 10.1121/1.2987426
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of the fundamental shear horizontal mode in a plate when incident at a through crack aligned in the propagation direction of the mode

Abstract: A study of the scattering of the fundamental guided wave SH 0 at a through-thickness narrow notch directed along the wave's propagation in a plate is presented. The results are obtained from Finite Element simulations and experimental measurements. Good agreement is found between the simulations and the measurements. The results are shown for a range of crack lengths and shapes. The scattered wave field consists of the reflected and diffracted SH 0 mode and also contributions from mode conversions to the S 0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…Such complex wave scattering requires a combination of advanced non-contact visualization techniques to characterize scattered wave fields from defects such as experimental models and computational simulations. Some excellent visuals of scattering of compression and shear wave modes from axially and normally aligned cracks, finite slits and notches are provided in Staszewski et al (2007) and Ratassepp et al (2008). In these cases, the experimental models are significantly large such that mode interference is minimized by the separation achieved with the different speeds at which modes travel through the structure.…”
Section: Plate Wave Solutionsmentioning
confidence: 98%
“…Such complex wave scattering requires a combination of advanced non-contact visualization techniques to characterize scattered wave fields from defects such as experimental models and computational simulations. Some excellent visuals of scattering of compression and shear wave modes from axially and normally aligned cracks, finite slits and notches are provided in Staszewski et al (2007) and Ratassepp et al (2008). In these cases, the experimental models are significantly large such that mode interference is minimized by the separation achieved with the different speeds at which modes travel through the structure.…”
Section: Plate Wave Solutionsmentioning
confidence: 98%
“…The concept was demonstrated by monitoring the metal loss due to general corrosion and sand erosion in aircraft structures. Cawley [11][12] studied the characteristics of pulse-echo reflection of the SH0 wave from part-thickness elliptical defects in plates via finite element analysis and experimental measurements. It was shown that the reflection ratio spectrum of the SH0 mode from an elliptical defect exhibited a periodic pattern due to interference between reflections from the two edges of the defect.…”
Section: Introductionmentioning
confidence: 99%
“…the fundamental symmetric wave (S0) and shear horizontal wave (SH0). Previous studies [12,13] have considered SH0 Lamb wave propagation due to its non-dispersive properties, however, experimentally exciting only the SH0 wave is difficult compared to exciting S0. In this study, only S0 Lamb wave excitation will be considered.…”
Section: Computational Set-up and Proceduresmentioning
confidence: 99%
“…The scattered wave fields when an incident elastic wave impinges on a crack have been investigated for bulk waves [9][10][11], and more recently, for Lamb waves [12,13]. It is known that an infinitesimal crack is equivalent to a point source consisting of body-force doublets with different forcing combinations that correspond to different crack opening modes [14].…”
mentioning
confidence: 99%